Factors Affects The Income of Street Sellers in Kuta Alam - Talbani Farlian; Siti Lutfiah Novitri; Meutia Handayani (BALANCE: Economic, Business, Management and Accounting Journal, 2022)
This study aims to determine the effect of capital, age of business, and working hours on the income of street sellers in Kuta Alam. This research is quantitative, namely research that aims to obtain evidence of a hypothesis; Data was collected through interviews and direct observation; The sample used was 20 respondents using random sampling technique; Data analysis technique using multiple linear regression. The results showed that when testing the partial regression coefficient with = 5%, of the three variables (capital, company age, and working hours) only capital had a significant effect on the income of street sellers.